SPECTRUM, VELOCITY AND DRIFT OF DROPLETS SPRAYED BY NOZZLES WITH AND WITHOUT AIR INDUCTION AND MINERAL OIL - França,Jorge A. L. (2017)
ABSTRACT The aim of this study was to evaluate the spectrum, the velocity and the potential drift risk of droplets sprayed by nozzles with and without air induction, with the addition of mineral oil to the spray solution. The experiment was conducted in a completely randomized design with five replications; in a factorial model 2 × 2 (two spray nozzles and spray solution with and without mineral oil Assist®). Spray nozzles with and without air induction were evaluated, with nominal flow rate of 1.14 L min−1 and pressure of 300 kPa. The spectrum and the velocity of droplets were evaluated directly, using a droplet analyzer (VisiSize D30) in real time based on the analysis of high-resolution images. The drift potential was evaluated in an open circuit wind tunnel. The data were submitted to analysis of variance and comparison test. In general, the addition of mineral oil (1.5% V V−1) resulted in an increase in the velocity of droplets, reduced drift and more homogeneous droplet spectrum. Air induction nozzles promoted larger and less homogeneous droplets, but they little affected the velocity of the droplets. There is an inverse correlation between drift potential and volume median diameter (VMD), which indicates that VMD can be used to predict the behavior of drift risk.